Public Culture, Sociality, and Listening to Jazz: Aural Memorialisation in the Time of COVID - Pyper, Brett (Kronos: Southern African Histories, 2024)
Taking its cue from two instances of hyper-local jazz sociability along one street in Mamelodi, five years apart, the focus of this article is on three instances of public memorialisation and, through them, on how listening can be socialised and enculturated. It is an exploration both of how sociality is co-constituted through listening, and of how listening is socially constructed, attending to how people become members of aural collectives in distinctive ways. It foregrounds how mostly working-class people living under conditions seldom of their own making continue, in the avowedly postapartheid context, at least partially to remake their worlds sonically, foregrounding the public cultures that they thereby aurally co-create as a notable cultural expression in and of themselves. Methodologically, it considers how recourse to non-elite aesthetics, viewed as repertoires of living, offer alternatives to the claims of both ethnographies and social histories ‘from below’ to present ‘the word’ of the community’ in an authoritative sense.